2019
DOI: 10.5607/en.2019.28.4.474
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Topographical Patterns of Spike-Wave Discharge in Transgenic and Pharmacologically Induced Absence Seizure Models

Abstract: Absence seizures (AS) are generalized non-convulsive seizures characterized by a brief loss of consciousness and spike-and-wave discharges (SWD) in an electroencephalogram (EEG). A number of animal models have been developed to explain the mechanisms of AS, and thalamo-cortical networks are considered to be involved. However, the cortical foci have not been well described in mouse models of AS. This study aims to use a high density EEG in pathophysiologically different AS models to compare the spatiotemporal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The brain functional connectivity is reduced in asymptomatic carriers of LRRK2 mutations and progressively becomes exacerbated at the clinical onset of PD [ 44 , 45 ]. Slowing neuronal oscillation is associated with seizure or epileptiform like events [ 46 , 47 ]. Collectively this indicates the presence of the mutations is sufficient to induce significant functional changes within neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The brain functional connectivity is reduced in asymptomatic carriers of LRRK2 mutations and progressively becomes exacerbated at the clinical onset of PD [ 44 , 45 ]. Slowing neuronal oscillation is associated with seizure or epileptiform like events [ 46 , 47 ]. Collectively this indicates the presence of the mutations is sufficient to induce significant functional changes within neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, absence seizures in GAERS rats are abolished by blocking the firing of these neurons ( Polack et al ., 2009 ), and are more susceptible to ethosuximide applied in the primary somatosensory cortex than the motor cortex or ventrobasal thalamus ( Richards et al , 2003 ; Manning et al , 2004 ). Notably, a recent study ( Lee et al , 2019 ) has shown that whereas spontaneous SWD in PLC-β4 knockout mice originate in the somatosensory cortex, the majority of SWD in the pharmacological γ-hydroxybutyric acid (GHB) model ( Snead, 1992 ; Venzi et al , 2015 ) appear first in the prefrontal cortex, indicating different sites of SWD initiation in different mouse and rat, genetic and pharmacological models as in children with absence seizures (see below).…”
Section: Introductionmentioning
confidence: 99%
“…non-epileptic) animal. Moreover, investigations of absence seizure initiation should carefully consider the different location of the CIN among animal models ( Meeren et al , 2002 ; Studer et al , 2018 ; Lee et al , 2019 ) and between models and children with absence seizures ( Bai et al , 2010 ; Guo et al , 2016 ; Tangwiriyasakul et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution of the mouse HD-EEG can be compared to that of the human HD-EEG, providing comparative neuroimaging between the two species. We have proven the use of mouse HD-EEG for retrieving local and global cortical activities, including the somatosensory and motor cortex 19 , prefrontal cortex 1 , anterior versus posterior spindles 20 , and global versus local seizures 21 . Among these studies, we previously provided a full dataset of evoked auditory stimulation under time-locked optogenetic stimulation 22 .…”
Section: Background and Summarymentioning
confidence: 99%